2014
DOI: 10.1016/j.jocn.2013.11.048
|View full text |Cite
|
Sign up to set email alerts
|

Ataxia with oculomotor apraxia type 2 fibroblasts exhibit increased susceptibility to oxidative DNA damage

Abstract: Ataxia with oculomotor apraxia type 2 (AOA2) is an autosomal recessive cerebellar ataxia associated with mutations in SETX, which encodes the senataxin protein, a DNA/RNA helicase. We describe the clinical phenotype and molecular characterization of a Colombian AOA2 patient who is compound heterozygous for a c.994 C>T (p.R332W) missense mutation in exon 7 and a c.6848_6851delCAGA (p.T2283KfsX32) frameshift deletion in SETX exon 21. Immunocytochemistry of patient-derived fibroblasts revealed a normal cellular d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 29 publications
(30 reference statements)
0
8
0
Order By: Relevance
“…Another published study reported a role for the SPG48 protein KIAA0415 in DNA repair . Since KIAA0415 coprecipitates with spastizin and spatacsin, we investigated the induction of, and recovery from, DNA damage induced in fibroblasts with H 2 O 2 , using an alkaline comet assay . We observed no differences among the cell lines, indicating that spastazin is dispensable for DNA repair (Fig.…”
Section: Resultsmentioning
confidence: 88%
“…Another published study reported a role for the SPG48 protein KIAA0415 in DNA repair . Since KIAA0415 coprecipitates with spastizin and spatacsin, we investigated the induction of, and recovery from, DNA damage induced in fibroblasts with H 2 O 2 , using an alkaline comet assay . We observed no differences among the cell lines, indicating that spastazin is dispensable for DNA repair (Fig.…”
Section: Resultsmentioning
confidence: 88%
“…Moreover, SETX mutant mice display defective meiosis and Spo11-mediated DSB persistence 20 . Finally, depletion of senataxin/Sen1p triggers sensitivity to some DNA damaging agents such as H 2 O 2 and UV 21 23 , a feature also observed in AOA2 patient cell lines 22 , 24 , 25 . However, senataxin depleted cells are not radiation sensitive 22 , suggesting that it may not function at sites of DNA double-strand break (DSB), a form of DNA damage largely induced upon irradiation.…”
Section: Introductionmentioning
confidence: 72%
“…To track SETX subcellular localization, we developed a GFP-tagged, full-length expression construct. We tested if SETX might show nucleolus localization, based upon initial yeast Sen1p experimentation [26,27]. There is growing interest in the nucleolus, as disruption of this structure has been implicated in ALS linked to mutations in various RNA-binding proteins and C9orf72 dipeptide repeats [28,29].…”
Section: Setx Over-expression In Hek293a Cells Linked With Nucleolus Dissolutionmentioning
confidence: 99%